Note on the Indian barracudina Magnisudis indica (Ege, 1953) from Dongsha Atoll, South China Sea, with comments on adult tooth loss (Family Paralepididae) - Ho, Hsuan-Ching; Li, Hsin-Hui; Lin, Chien-Hsiang (Zootaxa, 2026)
Recent investigations of bottom-trawl bycatch around Dongsha Atoll, Taiwan, South China Sea have yielded numerous new records and undescribed fish species. Among the specimens collected, an unexpectedly large number of the Indian barracudina, Magnisudis indica (Ege, 1953), were obtained. Among its congeners in the family, M. indica is readily distinguishable by possessing the lowest number of total vertebrae (60–62). The adults of this species were extremely rare and by using these new adult materials we document intraspecific morphological variation in this species. Moreover, all examined specimens exhibit a strongly reduced or absent dentition on the jaws, gill rakers, and pharyngeal arches. This reduction of dentition reported here for M. indica may represent an ontogenetic condition in adults.